Initial experience with using frameless image-guided radiosurgery for the treatment of brain metastases - Liepa, Z.; Auslands, K.; Apskalne, D.; Ozols, R. (Experimental Oncology, 2012)
Aim : Recent technologic advances have led to the development of frameless radiosurgery. We report our initial results using frameless image-guided radiosurgery for the management of brain metastases. Methods: Over a 2-year period, 16 patients harboring 28 lesions were treated in our institution. 12 of 16 patients were treated in a single fraction, but 4 patients were treated using fractioned stereotactic radiotherapy in 3–5 fractions. The maximum target diameter, as determined by T1 — weighted contrast — enhanced magnetic resonance imaging were < 4 cm in all patients. 8 patients (50%) received WBRT (3 Gy in 10 fractions to a total dose of 30 Gy) prior to stereotactic radiosurgery, and were treated with SRS for either lesion progression or new lesions. The total treatment volume for each patient was the sum of the treatment volumes for all treated metastases. The median total treatment volume was 18.63 cm3 (range 1,85–47.03 cm3). Results: Median overall survival time of entire group were 10 months (95% confidence interval 7.470–12.530 months). Of the 3 (11.11%) lesions that showed complete response, all were associated with breast cancer. Partial response was seen in 8 (29.62%) cases. Stable disease was seen in 13 (48.14%) cases, but 3 (11.11%) cases showed progression of disease. Conclusion: Further studies are needed to to match the treatment results with other available modalities to optimize and individualize care of patients with brain metastases.